The effect of temperature and packaging on the physical quality of purple eggplant fruit (Solanum melongena L.) - Agus Agus; Dewi Firnia; Kiki Roidelindho; Andi Apriany Fatmawaty (Universitas Muhammadiyah Mataram, 2026)
Purple eggplant (Solanum melongena L.) can maintain its physical quality only at an interval of 3-4 days at room temperature. The perishable nature of purple eggplants can be reduced by temperature and packaging treatments to maintain their quality, especially in efforts to extend shelf life. This study aims to analyze the effect of temperature and packaging on the physical quality of purple eggplant. The study employed a factorial Split-Plot Design with two factors and was conducted with two replications. The first factor is storage temperature, which is divided into 4 levels, including S1 = 4°C, S2 = 6°C, S3 = 8°C, and S4 = 10°C. The second factor is the type of packaging, which is divided into 3 levels, namely, K1 = Plastic wrapping (wrap), K2 = High-Density Polyethylene (HDPE) Plastic, and K3 = Styrofoam. Each replication consists of 6 pieces, so the number of purple eggplants used is 24. The observed parameters included weight loss (%), hardness (mm/g/s), color, and pH. The results showed that the combination of 8°C temperature and plastic wrap packaging was the best treatment to suppress weight loss and maintain the dark purplish red color and fruit hardness until 28 Days After Harvest (DAP). Although 10°C temperature produced the highest pH value, the use of 8°C temperature with plastic wrap proved to be the most effective in maintaining the physical quality of purple eggplant fruit during cold storage.